Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/ani10071222
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study toward a Rapid Assessment of Age-Related Behavioral Differences in Family Dogs

Abstract: Over the last few years, several efforts have been undertaken to characterize the aging process in dogs. In the present study, we evaluate a short protocol measuring dogs’ cognitive, social, and physical capacities. Our aim was to develop a feasible test battery, with minimal pre-training requirements, no complex devices, and which is set outdoors (i.e., a specific testing room is not needed). As ageing in dogs is usually associated with a decrease in activity, we also assessed the personality trait activity/e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 27 publications
2
18
1
Order By: Relevance
“…Beyond these studies, the majority of the literature examining age-related changes in dog behaviour (e.g. 45 ), cognition (e.g. 46 ), brain anatomy (e.g., 47 ) or neural processes (e.g., 7 ), consists of studies with ‘adult’, i.e., 12-month-old or older animals or declare that dogs older than 12 months of age are adults (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond these studies, the majority of the literature examining age-related changes in dog behaviour (e.g. 45 ), cognition (e.g. 46 ), brain anatomy (e.g., 47 ) or neural processes (e.g., 7 ), consists of studies with ‘adult’, i.e., 12-month-old or older animals or declare that dogs older than 12 months of age are adults (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The wide range of expected lifespans, a natural risk to develop dementia, and an environment shared with humans, has also made dogs a promising model organism in aging research (for a review see [10]). Since laboratory dogs represent a limited sample of the natural genetic and environmental variability found in human populations and companion (or pet) dogs, the latter has gained more popularity in aging research recently [11][12][13][14][15][16][17][18]. Their behavior also differs from that of laboratory dogs [19] in ways that make the companion dog a more ecologically valid model of human aging.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, behavioural and physical deficits in old age have become more prevalent. In the last decades, research on canine ageing has grown exponentially as both scientists and the public have increasingly recognised dogs’ emotional, economic, and scientific value as an animal model species 2 5 . Studies have shown that owners of ageing pet dogs often report a decline in the dogs’ visual and auditory function, changes in social behaviour 6 12 , and the sleep/wake cycle 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently a battery of standardised outdoor behavioural tests (Mini Mental Test, MMT) was developed to allow the rapid assessment of age-related behavioural differences in family dogs 2 . Older dogs displayed less social interest, poorer spatial memory, and seemed less interested in and less fearful of a novel, moving object 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation